2018
DOI: 10.1074/jbc.m117.805689
|View full text |Cite
|
Sign up to set email alerts
|

The outer-membrane protein TolC of Vibrio cholerae serves as a second cell-surface receptor for the VP3 phage

Abstract: Receptor recognition is a key step in the initiation of phage infection. Previously, we found that VP3, the T7 family phage of the Vibrio cholerae serogroup O1 biotype El Tor, can adsorb to the core oligosaccharide (OS) of lipopolysaccharides of V. cholerae. However, some wild-type strains of V. cholerae possessing the intact OS gene cluster still have VP3 binding but are resistant to VP3 infection. Moreover, an OS gene deletion mutant still exhibits weak VP3 binding, suggesting multiple factors are possibly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…It has been shown that phage TLS selects for tolC mutants that are hypersensitive to novobiocin (13). Moreover, TolC has been identified as a phage receptor in other Gram-negative pathogens (14,15), giving further support to the combined use of phage and antibiotics. Similarly, the phage OMKO1 may be able to use multiple binding targets to infect P. aeruginosa, including the type IV pilus and the multidrug efflux pump MexAB/MexXY (7); both mechanisms can result in selection against drug resistance.…”
mentioning
confidence: 99%
“…It has been shown that phage TLS selects for tolC mutants that are hypersensitive to novobiocin (13). Moreover, TolC has been identified as a phage receptor in other Gram-negative pathogens (14,15), giving further support to the combined use of phage and antibiotics. Similarly, the phage OMKO1 may be able to use multiple binding targets to infect P. aeruginosa, including the type IV pilus and the multidrug efflux pump MexAB/MexXY (7); both mechanisms can result in selection against drug resistance.…”
mentioning
confidence: 99%
“…It has been shown that phage TLS selects for tolC mutants that are hypersensitive to novobiocin 13 . Moreover, TolC has been identified as a phage receptor in other Gram-negative pathogens 14,15 , giving further support to the combined use of phage and antibiotics. Similarly, the phage OMKO1 may be able to use multiple binding targets to infect P.a., including the type-IV pilus and the multidrug efflux pump, MexAB/MexXY 7 , both mechanisms can result in selection against drug resistance.…”
Section: Introductionmentioning
confidence: 88%
“…For a bacterial two-hybrid assay, the recombinant plasmids pKT25- epsD and pUT18C-gp20 were constructed as previously described ( Fan et al., 2018 ). Briefly, two putative interacting proteins (EpsD and gp20) were genetically fused to two complementary fragments, T25 and T18, of the active domain of adenylate cyclase (CyaA) from Bordetella pertussis ( Ladant, 1988 ).…”
Section: Methodsmentioning
confidence: 99%